Combining all-trans retinoid acid treatment targeting myeloid-derived suppressive cells with cryo-thermal therapy enhances antitumor immunity in breast cancer - Lou, Yue; Peng, Peng; Wang, Shicheng; Wang, Junjun; Du, Peishan; Zhang, Zelu; Zheng, Jiamin; Liu, Ping; Xu, Lisa X. (Frontiers in Immunology, 2022)
Targeting myeloid-derived suppressive cells (MDSCs) has been considered a potential strategy in tumor therapy. However, a single drug targeting MDSCs remains a challenge in the clinic. An increasing number of studies have shown that combination agents targeting MDSCs and immunotherapy may provide exciting new insights and avenues to explore in tumor therapy. In our previous study, a novel cryo-thermal therapy was developed for metastatic tumors that systematically activated innate and adaptive immunity. Moreover, cryo-thermal therapy was shown to dramatically decrease the levels of MDSCs and induce their differentiation toward potent antigen-presenting cells. However, the therapeutic effects of cryo-thermal therapy on the 4T1 mouse breast cancer model was still not satisfactory because of the high level of MDSCs before and after treatment. Therefore, in this study, we combined cryo-thermal therapy with all trans retinoid acid (ATRA), a small molecule drug that can induce the inflammatory differentiation of MDSCs. We found that combination therapy notably upregulated the long-term survival rate of mice. Mechanically, combination therapy promoted the phenotype and functional maturation of MDSCs, efficiently decreasing suppressive molecule expression and inhibiting glutamine and fatty acid metabolism. Moreover, MDSCs at early stage after combination therapy significantly decreased the proportions of Th2 and Treg subsets, which eventually resulted in Th1-dominant CD4+ T-cell differentiation, as well as enhanced cytotoxicity of CD8+ T cells and natural killer cells at late stage. This study suggests a potential therapeutic strategy for combination ATRA treatment targeting MDSCs with cryo-thermal therapy to overcome the resistance of MDSC-induced immunosuppression in the clinic.